Analisis Peranan PPKn Dalam Pengembangan Sikap Toleransi dan Penerimaan Keberagaman di Kalangan Mahasiswa FIS UNIMED - Talita Sembiring; Putri Widia Ningsih; Salwa Andini; Reylan Silverius Sinaga; Murniwati Lase (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The aim of this research is to analyze the role of Pancasila and Citizenship Education (PPKn) in forming an attitude of tolerance and acceptance of diversity among students at the Faculty of Social Sciences, Medan State University (FIS UNIMED) using qualitative research methods. . This research involves collecting data through interviews and in-depth observations of FIS UNIMED students. The research findings highlight the role of PPKn materials in better understanding the value of tolerance, the importance of respecting differences and efforts to build harmony between individuals. The analysis shows that citizenship education plays an important role in shaping students' attitudes towards tolerance and acceptance of diversity, but also highlights the expansion of materials and more inclusive approaches to deepen understanding and concrete actions to achieve equality and advance social conditions in the university environment. The implications of this research provide a strong foundation for developing PPKn programs that are more holistic and relevant in facing the increasingly complex challenges of diversity in society.